Vegetation Stratification in Semarang Coastal Area - Nana Kariada Tri Martuti; Yustinus Ulung Anggraito; Septiana Anggraini (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
The coastal region is a dynamic area as a transition between the land and the sea. The ecological function of the coastal area is affected mainly by the structure and composition of vegetation factors. This study aims to analyze the vegetation stratification of terrestrial to marine ecosystems in the coastal area of Semarang City, Central Java Indonesia as an effort to manage a sustainable ecosystem. A striped path combined with nested plots were applied in this research. The plots were placed by systematic purposive sampling based on the homogeneity of vegetation found along with the topographic conditions of the research location. Analysis of qualitative data used by way of inventorying plants and identifying plants based on morphological characteristics that can be observed. Data analysis was performed based on the results of an inventory of the structure and composition of vegetation obtained including the index of diversity, evenness, and species richness. The results of plant identification found in the three locations recorded 51 plant species consisting of 29 families. The different types of vegetation in Taman Lele, Tapak, and Tirang Beach affect the diversity, richness, and evenness index of vegetation in all three locations. Therefore, it can be concluded that different environmental factors contribute to the vegetation stratification from the land to the sea. This is the first report on the Semarang coastal area vegetation stratification. The results can have a positive impact on the coastal area conservation strategy for sustainable management, as well as to be a media for environmental education purpose.